New development of marine spatial planning in China: problems and policy suggestions on the implementation of National Plan for Main Functional Zones of Oceans. Issue 1 (20th April 2022) - Tang, Honghao; Lin, Mingyue; Yu, Jing; Yue, Qi
Abstract : Purpose: The focus of this paper is to further improve the implementation safeguard measures of the National Plan for Main Functional Zones of Ocean (NPMFZO) based on the implementation status of the national marine main functional area plan after the promulgation of the existing marine planning implementation safeguard measures, aiming at the problems existing in the implementation of the plan, to help the implementation of the plan more effective. Design/methodology/approach: This paper reviews the historical process of the preparation and implementation of NPMFZO, analyzes the problems existing in the implementation of this plan, and puts forward some measures and suggestions under the background of the new national territory planning system. Findings: In the new period, the authors should focus on building the evaluation system of planning implementation, strengthening the coordination with other plans, improving the supporting policies of planning and ensuring the effective implementation of the main functional zoning of oceans under the territorial spatial planning system. Originality/value: This paper reviews some problems existing in the implementation of the NPMFZO and puts forward policy suggestions to ensure the implementation of the plan in the new period.